The Great Seljuqs : a History. - Basan, Osman Aziz (Routledge Studies in the History of Iran and Turkey, 2010)
Provides a broad history of the Seljuq Turks from their origins and early conquests in the 10th century, through the rise of empire until its dissolution at the end of the 12th. This book examines the corpus of academic work on the period and how Turkish historiography has interpreted and understood the Seljuqs.